ANALISIS KESALAHAN BERBAHASA (ERROR ANALYSIS) DALAM MEDIA PEMBELAJARAN BAHASA ARAB - Muhammad Ibrahim (Universitas Muhammadiyah Makassar, 2017)
This study aims to analyze the errors occurred in designing of Arabic learning media, covering the errors in both terms of language and in terms of learning media itself. This research was purposed at V (fifth) semester students of Arabic language study program of academic year 2016-2017 who are in the process of becoming prospective teacher of Arabic language. The methods used in order to collect data related to the problems were semi-structured interviews and in-depth observation. Interview was addressed to the students, while in-depth observation was used to observe the Arabic learning media made by the students. The results of this study indicated that the types of language errors made by students in the medium of learning Arabic language, including the level of error writing or harokat for example, error of pronunciation ةٌin ةٌَزِطَال word should be / /ًَزِطَال , misuse of the form of the word example, in the form of the word العظم not be found the same word form in Arabic, misuse of sentence order for example in the word واحد الظاع which should use pattern and form of character and mausuf, where the second word followed the first word pattern both in terms of its kind and its ta'rif ( الواحد الظاع ) and errors on the meaning of the word for example, durian images to describe the word بابايا . Meanwhile, if viewed from the aspect of performance, language errors could be categorized on misformation and misordering. Keywords: error in language, media, learning